DISTRIBUTION OF WEALTH FOR WIVES AND ADOPTED CHILDREN PERSPECTIVE OF YOGYAKARTA CUSTOMARY LAW - Robiatus Siddigiyah; Abdul Halim (International Conference on Humanity Education and Society (ICHES), 2023)
uThis unique research was conducted in Krapyak Village, Pundong District, Bantul Regency, Yogyakarta. This study uses a qualitative research method of visual analysis combined with interviews with heirs of relatives of the heirs of the heads of neighborhood associations and heads of neighborhood associations in the area who respond to the distribution of inheritance according to customary law in force in Krapyak Village that the inheritance is distributed to one-eighth wife valid for life alive, after the wife dies, the property is returned to the heir, while the adopted child is the biological child of the heir, usually called a nephew, and the remaining property is seven-eighth.